A Review of the Prophetic Hadith on Suicide and Its Implications for Prevention among Adolescents - Muhammad Ali; Sitti Asiqah Usman Ali; Abd. Bashir Fatmal; La Ode Ismail Ahmad (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Suicide is a serious mental health issue that affects many adolescents around the world, including Muslims. Although Islamic teachings strictly prohibit suicide, the phenomenon persists, indicating a gap between religious teachings and the reality faced by adolescents. Various factors, such as academic pressure, identity conflict, and the influence of social media, contribute to the increased risk of suicide among adolescents. This study aims to explore the hadith perspective on suicide and develop a prevention model based on Islamic teachings, with a focus on adolescents. The method used in this study is qualitative with a descriptive analysis approach. Data were collected through a literature study that delved into hadith related to suicide, as well as literature that discussed psychological factors such as depression, anxiety, and stress. This approach allowed the researcher to provide a comprehensive understanding of Islamic teachings and the factors that influence suicidal behavior. The results show that the traditions that discuss suicide are of authentic quality and provide strong moral guidance. They emphasize the prohibition of suicide and teach the importance of valuing life and finding solutions to difficulties. In addition, this study found that the integration of psychological and spiritual approaches in addressing the problem of suicide is still less than optimal. This study recommends the development of a suicide prevention model that integrates hadith values with psychological approaches. By creating a supportive environment, comprehensive religious education, and adequate psychological support, it is expected to reduce the suicide rate among Muslim adolescents. These efforts are essential to building better mental resilience and creating a healthier and more productive generation.